Appetite change profiles in depression exhibit differential relationships between systemic inflammation and activity in reward and interoceptive neurocircuitry - Cosgrove, K.T. (Brain Behav Immun, 2019)
Appetite change is a defining feature of major depressive disorder (MDD), yet little neuroscientific evidence exists to explain why some individuals experience increased appetite when they become depressed while others experience decreased appetite. Previous research suggests depression-related appetite changes can be indicative of underlying neural and inflammatory differences among MDD subtypes. The present study explores the relationship between systemic inflammation and brain circuitry supporting food hedonics for individuals with MDD. Sixty-four participants (31 current, unmedicated MDD and 33 healthy controls [HC]) provided blood samples for analysis of an inflammatory marker, C-reactive protein (CRP), and completed a functional magnetic resonance imaging (fMRI) scan in which they rated the perceived pleasantness of various food stimuli. Random-effects multivariate modeling was used to explore group differences in the relationship between CRP and the coupling between brain activity and inferred food pleasantness (i.e., strength of the relationship between activity and pleasantness ratings). Results revealed that for MDD with increased appetite, higher CRP in blood related to greater coupling between orbitofrontal cortex and anterior insula activity and inferred food pleasantness. Compared to HC, all MDD exhibited a stronger positive association between CRP and coupling between activity in striatum and inferred food pleasantness. These findings suggest that for individuals with MDD, systemic low-grade inflammation is associated with differences in reward and interoceptive-related neural circuitry when making hedonic inferences about food stimuli. In sum, altered immunologic states may affect appetite and inferences about food reward in individuals with MDD and provide evidence for physiological subtypes of MDD.